The Developmental & Molecular Requirements for Ensuring that Human Pluripotent Stem Cell-Derived Hair Follicle Bulge Stem Cells Have Acquired Competence for Hair Follicle Generation Following Transplantation. (28th May 2021) - Ibrahim, Michel R.; Medhat, Walid; El-Fakahany, Hasan; Abdel-Raouf, Hamza; Snyder, Evan Y.
When using human induced pluripotent stem cells (hiPSCs) to achieve hair follicle (HF) replacement, we found it best to emulate the earliest fundamental developmental processes of gastrulation, ectodermal lineage commitment, and dermogenesis. Viewing hiPSCs as a model of the epiblast, we exploited insights from mapping the dynamic up- and down-regulation of the developmental molecules that determine HF lineage in order to ascertain the precise differentiation stage and molecular requirements for grafting HF-generating progenitors. To yield an integrin-dependent lineage like the HF in vivo, we show that hiPSC derivatives should co-express, just prior to transplantation, the following combination of markers: integrins α6 and β1 and the glycoprotein CD200 on their surface; and, intracellularly, the epithelial marker keratin 18 and the hair follicle bulge stem cell (HFBSC)-defining molecules transcription factor P63 and the keratins 15 and 19. If the degree of trichogenic responsiveness indicated by the presence of these molecules is not achieved (they peak on Days 11-18 of the protocol), HF generation is not possible. Conversely, if differentiation of the cells is allowed to proceed beyond the transient intermediate progenitor state represented by the HFBSC, and instead cascades to their becoming keratin 14 + keratin 5 + CD200 – keratinocytes (Day 25), HF generation is equally impossible. We make the developmental case for transplanting at Day 16-18 of differentiation—the point at which the hiPSCs have lost pluripotency, have attained optimal expression of HFBSC markers, have not yet experienced downregulation of key integrins and surface glycoproteins, have not yet started expressing keratinocyte-associated molecules, and have sufficient proliferative capacity to allow a well-populated graft. This panel of markers may be used for isolating (by cytometry) HF-generating derivatives away from cell types unsuited for this therapy as well as for identifying trichogenic drugs.